The Influence of Entrepreneurial Resilience, AI Adoption, and Customer Engagement on the Sustainability of MSMEs - Junedi Junedi; Ida Abdul Gopar (Mandalika Institute, 2026)
The sustainability of MSMEs has become a critical issue amid growing uncertainty in the business environment, ongoing digital transformation, and shifts in consumer behavior. Although numerous studies have examined the factors influencing business continuity, research integrating entrepreneurial resilience, AI adoption, and customer engagement within a single research model remains limited, particularly in the context of MSMEs in Indonesia. This study aims to analyze the effects of entrepreneurial resilience, AI adoption, and customer engagement on the sustainability of MSMEs. A quantitative approach was employed using a survey of 100 micro, small, and medium enterprise owners in Bekasi Regency. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that entrepreneurial resilience (β = 0.225, p = 0.004), AI adoption (β = 0.297, p = 0.003), and customer engagement (β = 0.479, p < 0.001) each have positive and significant effects on MSME sustainability. The regression model explains 71.2% of the variance in business sustainability (R² = 0.712) and is statistically significant (F = 79.258, p < 0.001). These results indicate that entrepreneurs’ adaptive capabilities, effective AI utilization, and active customer participation are essential drivers of sustainable business performance. Theoretically, this study contributes to the entrepreneurship and MSME sustainability literature by providing an integrated empirical model that simultaneously examines entrepreneurial resilience, AI adoption, and customer engagement as complementary determinants of long-term business sustainability in the digital era.